2017
DOI: 10.1016/j.celrep.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

EBI2 Expression and Function: Robust in Memory Lymphocytes and Increased by Natalizumab in Multiple Sclerosis

Abstract: The interaction between oxysterols and the G protein-coupled receptor Epstein-Barr virus-induced gene 2 (EBI2) fine-tunes immune cell migration, a mechanism efficiently targeted by several disease-modifying treatments developed to treat multiple sclerosis (MS), such as natalizumab. We previously showed that memory CD4 T lymphocytes migrate specifically in response to 7α,25-dihydroxycholesterol (7α,25-OHC) via EBI2 in the MS murine model experimental autoimmune encephalomyelitis. However, the EBI2 expression pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 33 publications
4
56
1
Order By: Relevance
“…Another theory describes the potential for EBV to preferentially drive proinflammatory B cell cytokine responses [e.g., tumor necrosis factor (TNF), lymphotoxin (LT), IL-6, and granulocyte-macrophage colony-stimulating factor (GM-CSF) expression] [40,41] and interfere with the downregulatory function of IL-10. Another theory based on the ability of EBV to induce expression of EBV-induced G protein-coupled receptor 2 (EBI2/ GPR183) [42][43][44][45] supports, in part, migration of autoreactive T cells and EBV-infected B cells into the CNS.…”
Section: Box 1 Ebv Involvement Across the Ms Spectrummentioning
confidence: 99%
“…Another theory describes the potential for EBV to preferentially drive proinflammatory B cell cytokine responses [e.g., tumor necrosis factor (TNF), lymphotoxin (LT), IL-6, and granulocyte-macrophage colony-stimulating factor (GM-CSF) expression] [40,41] and interfere with the downregulatory function of IL-10. Another theory based on the ability of EBV to induce expression of EBV-induced G protein-coupled receptor 2 (EBI2/ GPR183) [42][43][44][45] supports, in part, migration of autoreactive T cells and EBV-infected B cells into the CNS.…”
Section: Box 1 Ebv Involvement Across the Ms Spectrummentioning
confidence: 99%
“…1a) in human peripheral blood mononuclear cells (PBMC). 19 EBI2 expression was also observed in PBMCs without significant differences between healthy volunteers and IBD patients (CD and UC, Fig. 1b).…”
Section: Human Intestinal Lymphocytes Express Ebi2mentioning
confidence: 82%
“…Both oxysterols modulate the immune response, 25-OHC controls viral infection in macrophages ( 1 ) and 7α,25-OH promotes macrophage and B cell trafficking within lymphoid structures ( 2 ). We showed that 7α,25-OHC promotes memory CD4 + T cell migration to the target inflammatory organs during autoimmunity ( 3 , 4 ). While authors have proposed oxysterols as pro-inflammatory mediators, others have submitted 25-OHC as an anti-inflammatory intervener ( 5 ).…”
Section: Introductionmentioning
confidence: 99%